Medical Nutrition Therapy in Hospitalized Patients with Diabetes - Gosmanov, Aidar R. (2012)
Medical nutrition therapy (MNT) plays an important role in management of hyperglycemia in hospitalized patients with diabetes mellitus. The goals of inpatient MNT are to optimize glycemic control, to provide adequate calories to meet metabolic demands, and to create a discharge plan for follow-up care. All patients with and without diabetes should undergo nutrition assessment on admission with subsequent implementation of physiologically sound caloric support. The use of a consistent carbohydrate diabetes meal-planning system has been shown to be effective in facilitating glycemic control in hospitalized patients with diabetes. This system is based on the total amount of carbohydrate offered rather than on specific calorie content at each meal, which facilitates matching the prandial insulin dose to the amount of carbohydrate consumed. In this article, we discuss general guidelines for the implementation of appropriate MNT in hospitalized patients with diabetes.